Work Alienation Among Women in the Hospitality Sector in India - Mehta, Prashant; Banerjee, Jayanta (Prabandhan: Indian Journal of Management, 2025)
Purpose : The present study focused on identifying the factors influencing work alienation (WA) among women in 5-star hotels in India, with powerlessness as a mediator. The growing focus on equality, diversity, and inclusiveness prompted us to examine WA among women in the hospitality sector, which was considered to be one of the most stressful sectors to work in and where the participation of women has been increasing over time. Methodology : The study adopted a sequential mixed-method approach to examine the influence of leadership quality, offensive workplace behavior, and perceived informational justice on WA with powerlessness as a mediator. The analysis of data was performed using Smart PLS 4.0 software. Findings : We found that all three independent variables had a significant influence on WA. It was also found that powerlessness acted as a mediator between the three independent variables and WA. Practical Implications : It was recommended that hotels put in place a mechanism to ensure that information flows appropriately and transparently, leadership sensitization programs are initiated, and a mechanism is in place for psychological counseling to enable female employees to seek help in case the need arises. Our study was not free from limitations and allowed scope for future researchers to examine WA in hotels other than 5-star or those located in non-metro cities. Originality : Unlike prior research on WA that was limited to male industrial workers and operational jobs, this study examined the service industry, focusing on the hospitality sector and female employees.